Line Probe Assay for Monitoring Drug Resistance in Hepatitis B Virus-Infected Patients during Antiviral Therapy - Stuyver, Lieven (American Society for Microbiology, 2000)
Since the introduction of antiviral compounds such as lamivudine and famciclovir in the treatment schedules of patients with chronic hepatitis B virus (HBV) infection, the accumulation of a variety of mutations in the HBV polymerase gene has been observed. The selection of these mutations is generally considered the cause of viral nonresponsiveness and treatment failure. Therefore, the detection of these mutations is of clinical importance. Previously genotyped HBV strains isolated from treated and untreated patients were amplified with primers specific for the HBV polymerase region from amino acids 465 to 562. Amplified products were cloned into plasmid vectors. The clones were used as reference strains. A set of 38 highly specific oligonucleotide probes covering three different codon positions, L528M, M552V/I, and V/L/M555I, were selected. These probes were applied as 19 different lines on a membrane strip. The strips were then hybridized with PCR fragments from the reference panel, revealing the amino acids at the three codon positions simultaneously for each clone. PCR products generated from two patients infected with HBV genotypes A and C, respectively, and treated with nucleoside analogs were analyzed on these strips. A gradual increase in genetic HBV polymerase complexity was observed in follow-up samples compared to that in pretreatment samples. Additional analysis of HBV polymerase DNA fragments in recombinant plasmid clones demonstrated the existence of (i) clones with double mutations, (ii) clones with single mutations at either codon 528, 552, or 555, and (iii) the simultaneous occurrence of two or more viral populations within one sample. This line probe assay detected the complex quasispecies nature of HBV and provided some insight into the dynamics of resistance mutations.